(untitled) (Research, Society and Development, 2020)
This objective work aims to qualify the importance of Higher Education Institutions (HEIs) in the Metropolitan Region of Cariri (RMCariri), and how they act in the process of growth and economic and social development of the region. To do so, use a descriptive research methodology and secondary data collection. In this context, it was found that an RMCariri has been highlighted in the last decades, as a prosperous region and that attracted many investors and at the same time offering several opportunities for employment, education and leisure, for people, both from the region itself and also from others. neighboring regions. There is an important highlight for education, this region has significant economic growth and development and transforms the local reality. At the same time as the growth and development talks of RMCariri, it is clear that there is a huge economic and structural difference between the municipalities that make up this region, as is the case with the municipalities that form the CRAJUBAR triangle (Crato, Juazeiro do Norte and Barbalha). What is most of the investments directed to the region, are centralized in these three municipalities. As most of the investments are centralized in CRAJUBAR, also known as Higher Education Institutions (HEIs), they are also located in its main facilities in these three municipalities, or contribute to the educational training of people residing across the country, also for a empowerment of individuals. So, we concluded that, or CRAJUBAR, a region belonging to RMCariri, significantly reduced higher education in terms of the number of HEIs and this has been changing to improve the region’s economic and social growth and development process.